2022
DOI: 10.3389/fnana.2022.981426
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of human superficial fascia

Abstract: The superficial fascia has only recently been recognized as a specific anatomical structure. Furthermore, whereas it is actually recognized that the innervation of the deep/muscular fascia plays a key role in proprioception and nociception, there are very few studies that have analyzed these characteristics in the superficial fascia. In this work, our group analyzed two different anatomical districts (abdomen and thigh), from volunteer patients, undergoing surgery procedures. Each sample was processed for hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Below, the SF appeared as a thin fibrous layer ( Figure 1 b), with a membranous appearance and a multilayered structure of collagen bundles. The histological tangential section of the SF layer showed a net of irregularly arranged collagen fibers, interpenetrated by adipose clusters and crossed by a rich vascular pattern ( Figure 1 c), as already demonstrated and described in our previous works [ 23 , 28 ]. Beneath the SF, another layer of adipose tissue was visible—the DAT—with smaller, flatter, and less-defined adipose lobes than those of the SAT ( Figure 1 a).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Below, the SF appeared as a thin fibrous layer ( Figure 1 b), with a membranous appearance and a multilayered structure of collagen bundles. The histological tangential section of the SF layer showed a net of irregularly arranged collagen fibers, interpenetrated by adipose clusters and crossed by a rich vascular pattern ( Figure 1 c), as already demonstrated and described in our previous works [ 23 , 28 ]. Beneath the SF, another layer of adipose tissue was visible—the DAT—with smaller, flatter, and less-defined adipose lobes than those of the SAT ( Figure 1 a).…”
Section: Resultssupporting
confidence: 85%
“…According to Italian law, the parts of the body removed for therapeutic purposes during surgery that would otherwise be destined for destruction can be used for research. For each patient, 3 samples, of ~1 cm 2 were randomly collected from different areas of the abdominal region, at full thickness, from the epidermis to the DAT [ 23 ]. Moreover, from each subject, three additional samples of the superficial fascia were isolated from the surrounding adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Damage to unmyelinated small fibers in the early stages of CTS may increase thermal variation in areas innervated by the same nerve through mechanisms such as sympathetic dysfunction, reactive vasoconstriction, and antidromic sensory fiber activation [ 25 ]. Furthermore, a neuroanatomic study recently identified superficial fascia to be innervated by autonomic and sensory nerve fibers, which suggests the role of superficial fascia stress in CTS [ 26 ]. We have reported in a previous study that as the severity of CTS worsens, the anisometry also gradually increases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic rigidity of this fascia increases the stiffness of the inter-metatarsal space, leading to entrapment of the CDPN. Further, the same authors have reported more recently that the deep fasciae are very well innervated [ 8 , 9 ], and their alteration can be a further source of neuropathic chronic pain. Hence, stiffness of fascia in the foot could also irritate the free nerve endings inside the fascial tissue, causing an additional source of nociceptive pain [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%